2021
DOI: 10.1177/14644207211047376
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bending fatigue performances of selective laser sintered and injection moulded nylon spur gears

Abstract: This study compares the bending fatigue performance of a selective laser sintered Nylon 12 spur gear with an injection moulded Nylon 66 gear. Test gears were subjected to load-controlled, single tooth bending fatigue tests in a custom-built test setup. Cyclic pulsating loads were applied on the test gear using a steel driver gear. The bending fatigue life of selective laser sintered gears was superior compared to the injection moulded gears. In the high cycle fatigue region, the difference between the fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The authors highlight the relatively poor accuracy of the tooth flank due to the low accuracy of the file and the relatively low accuracy of the PBF-LB/P process. Pandian et al (2022a) compare the flexural fatigue performance of spur gears manufactured with two types of Nylon through PBF-LB/P (using Nylon 12) and traditional plastic injection molding (IM) process (using Nylon 66). The results showed that PBF-LB/P gears have a longer flexural fatigue life in the high-cycle fatigue region than IM gears.…”
Section: Introductionmentioning
confidence: 99%
“…The authors highlight the relatively poor accuracy of the tooth flank due to the low accuracy of the file and the relatively low accuracy of the PBF-LB/P process. Pandian et al (2022a) compare the flexural fatigue performance of spur gears manufactured with two types of Nylon through PBF-LB/P (using Nylon 12) and traditional plastic injection molding (IM) process (using Nylon 66). The results showed that PBF-LB/P gears have a longer flexural fatigue life in the high-cycle fatigue region than IM gears.…”
Section: Introductionmentioning
confidence: 99%
“…This problem may be addressed by improving product design 6 and by better understanding of fatigue resistance of materials produced by DMLS. 7 The AM principle of layerwise building from melted powder particles creates more inhomogeneities in the microstructure of DMLS products than it is the case with traditional technologies. 8 The fundamental importance of the inhomogeneities for mechanical properties of materials was a motivation for concern and extensive studies of materials produced by DMLS.…”
Section: Introductionmentioning
confidence: 99%